Entrepreneurship in family and non-family business : youth perceptions and poverty reduction effects in Cameroon - Johannes Tabi Atemnkeng; Fomba Emmanuel Mbebeb; Mbu Daniel Tambi (The journal of accounting and management, 2017)
The current paper attempts to explain productivity performance between Family and Non-family Firms in Cameroon, and also to determine whether the relative contribution to the social and economic development of a country by family firms as opposed to non-family firms is related to differences in production technologies and production efficiency. The study made use of self-explorative survey which was collected using qualitative methods. Based on the qualitative survey, results showed that there exists some similarities between family and non-family firms, and at the same time some significant differences in performance between the two are unveiled in terms of profitability, income generation, job creation and poverty reduction. The paper provides evidence-based policy recommendations to enhance the productivity and competitiveness of family and nonfamily enterprises in Cameroon.
2668125-0; 2392-8778; The journal of accounting and management; 718053745